Effect of culture medium on propagation and phenotype of corneal stroma-derived stem cells - Sidney, Laura E.; Branch, Matthew James; Dua, Harminder S.; Hopkinson, Andrew (Elsevier, 2015)
Background: The limbal area of the corneal stroma has been identified as a source of mesenchymal-like stem cells, which have potential for exploitation as a cell therapy. However, the optimal culture conditions are disputed and few direct media comparisons have been performed. In this report, we evaluated several media types to identify the optimal for inducing an in vitro stem cell phenotype.